Public vs physician views of liability for artificial intelligence in health care. (19th April 2021) - Khullar, Dhruv; Casalino, Lawrence P; Qian, Yuting; Lu, Yuan; Chang, Enoch; Aneja, Sanjay
Abstract: The growing use of artificial intelligence (AI) in health care has raised questions about who should be held liable for medical errors that result from care delivered jointly by physicians and algorithms. In this survey study comparing views of physicians and the U.S. public, we find that the public is significantly more likely to believe that physicians should be held responsible when an error occurs during care delivered with medical AI, though the majority of both physicians and the public hold this view (66.0% vs 57.3%; P  = .020). Physicians are more likely than the public to believe that vendors (43.8% vs 32.9%; P  = .004) and healthcare organizations should be liable for AI-related medical errors (29.2% vs 22.6%; P  = .05). Views of medical liability did not differ by clinical specialty. Among the general public, younger people are more likely to hold nearly all parties liable.